Majulah! 50 years of Malay/Muslim community in Singapore - Zainul Abidin bin Rasheed; Norshahril Saat (World Scientific Series on Singapore's 50 years of nation-building, 2016)
The Malay/Muslim community is an integral part of the formative years of modern Singapore. The Singapore Malay/Muslim community comprises approximately 13% of Singapore's population of about 5.5 million people. More than 90% of Singaporean Muslims are Malays while the remaining are Indians, Arabs, Chinese and members of other ethnic groups. This book highlights the progress of the community, its contributions, and also the challenges for the last 50 years since 1965